A Taxonomy of Corporate Emergency Responsibility to Ensure Social Sustainability Post-shock - Aracil Fernández, Elisa María; Forcadell Martínez, Francisco Javier (Emerald (Londres, Reino Unido), 2022)
Extreme events undermine progress toward social sustainability and require an immediate response from the private sector. The authors propose a two dimensional framework (response time and the scope of activities to the various stakeholders) to benchmark firms’ effectiveness in mitigating the threats to social sustainability post-disaster.

Extreme events undermine progress toward social sustainability and require an immediate response from the private sector. The authors propose a two dimensional framework (response time and the scope of activities to the various stakeholders) to benchmark firms’ effectiveness in mitigating the threats to social sustainability post-disaster.
Capítulos en libros